Association Between Daily Steps at Moderate Cadence and Vascular Outcomes in Patients With Claudication. Issue 1 (January 2022) - Gardner, Andrew W.; Montgomery, Polly S.; Wang, Ming; Shen, Biyi
Abstract : Purpose: We determined whether patients with peripheral artery disease (PAD) and claudication grouped according to tertiles of community-based daily steps taken at a moderate cadence had differences in vascular function and biomarkers and whether group differences in vascular function and biomarkers persisted after adjusting for demographic variables, comorbid conditions, and severity of PAD. Methods: Two hundred sixty-three patients were evaluated for 1 wk on steps taken at a moderate cadence (exceeding 60 steps/min), and patients were placed into low (group 1), intermediate (group 2), and high (group 3) tertiles. Results: Ankle/brachial index (ABI) at 1 min after exercise (mean ± SD) was significantly higher in groups 2 and 3 than in group 1 in unadjusted ( P < .01) and adjusted ( P < .01) analyses (group 1: 0.34 ± 0.25; group 2: 0.38 ± 0.27; and group 3: 0.44 ± 0.28). Exercise time to reach the minimum calf muscle oxygen saturation (StO2 ) value during treadmill exercise was significantly longer in groups 2 and 3 than in group 1 in unadjusted ( P < .01) and adjusted ( P < .01) analyses (group 1: 127 ± 127 sec; group 2: 251 ± 266 sec; and group 3: 310 ± 323 sec). Fibrinogen was significantly lower in group 3 than in group 1 in unadjusted ( P = .02) and adjusted ( P = .05) analyses (group 1: 3.5 ± 1.2 g/L; group 2: 3.6 ± 1.5 g/L; and group 3: 3.0 ± 1.1 g/L). Conclusions: Compared with patients with claudication in the lowest tertile of community-based daily steps taken at a moderate cadence, patients in the second and third tertiles had better calf muscle StO2 and ABI values during and immediately after exercise. Second, the most active group had lower fibrinogen levels than the least active group. Abstract : Compared with patients with claudication in the lowest tertile of daily steps taken at moderate cadence, patients in the second and third tertiles had better calf muscle oxygen saturation, ankle/brachial index, and fibrinogen (third tertile only). Group differences persisted after adjusting for demographics, comorbidities, and peripheral artery disease severity.